The infinite jest: Heri Dono's Punakawan and their metamorphosis throughout Indonesia's new order regime and reformasi era - Syakirah Aqilah Binte Sanusi (Nanyang Technological University, 2024)
Why was wayang a popular visual iconography amongst all sociopolitical/cultural circles in post-independent modern Indonesia, particularly during the Suharto regime? What relationships are explored and fostered between artist-audience in a period where arts censorship was at an all-time high, versus a period where there was more freedom of expression? What is the ultimate role of visual (and consequently, performative) art during this tumultuous sociopolitical period? Following these questions, I argue that through the portrayal of environmental and bodily metamorphosis in Heri Dono’s works, his works are a vessel in which satirical sociopolitical commentary thrives given his reworking of the iconic punakawan figure. Ultimately, he privileges the metamorphosis of his punakawan to instil and embody the hopeful empowerment that the Indonesian public fought for in the late 1990s, from the New Order regime until the Reformasi era.